2017
DOI: 10.4172/2329-9002.1000186
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Susceptibility Genes for Powdery and Downy Mildew in Watermelon and Squash

Abstract: Powdery mildew (PM) caused by Podosphaera xanthii and downy mildew (DM) caused by Pseudoperonospora cubensis are two of the most economically important diseases for watermelon (Citrullus lanatus) and squash (Cucurbita pepo, C. maxima and C. moschata). Traditional breeding for resistance to PM and DM is resource intensive, often requiring decades' long phenotyping and selection processes. As an alternative, durable and broadspectrum resistance to PM and DM can be obtained through loss-of-function of susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…These genes probably have a conserved function across plant species. Schouten et al (2014) and Porterfield and Meru (2017) used DMR1 and DMR6 to search for novel DMR candidate genes in the Cucurbitaceae family. Huibers et al (2013) studied the DMR1 orthologue in S. lycopersicum (SIDMR1) and found that gene silencing was associated with resistance against late blight caused by the oomycete Phytophthora infestans, although it also caused detrimental effects on plant growth.…”
Section: Downy Mildewmentioning
confidence: 99%
“…These genes probably have a conserved function across plant species. Schouten et al (2014) and Porterfield and Meru (2017) used DMR1 and DMR6 to search for novel DMR candidate genes in the Cucurbitaceae family. Huibers et al (2013) studied the DMR1 orthologue in S. lycopersicum (SIDMR1) and found that gene silencing was associated with resistance against late blight caused by the oomycete Phytophthora infestans, although it also caused detrimental effects on plant growth.…”
Section: Downy Mildewmentioning
confidence: 99%
“…Then, a second series of k-mers (e.g. : narrow range, [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69], which revealed the best assembly performances, was scanned. Metrics for assessing the quality of a genome assembly (e.g.…”
Section: Sequencing Genome Assembly and Reference-guided Reconstructmentioning
confidence: 99%
“…DMR1 58 . PMR genes are involved in cell wall biology where they mediate structure formation and pectin accumulation 59 . Among them, the PMR5 family was the most represented, totalling from 67 to 69 gene members in the four inbred lines and 72 in CM334' , which were scattered along the genome.…”
mentioning
confidence: 99%
See 1 more Smart Citation